2013
DOI: 10.1088/0004-637x/777/2/125
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of the Number Density of Compact Galaxies

Abstract: We compare the number density of compact (small size) massive galaxies at low and high redshift using our Padova Millennium Galaxy and Group Catalogue (PM2GC) at z = 0.03 − 0.11 and the CANDELS results from Barro et al. (2013) at z = 1 − 2. The number density of local compact galaxies with luminosity weighted (LW) ages compatible with being already passive at high redshift is compared with the density of compact passive galaxies observed at high-z. Our results place an upper limit of a factor ∼ 2 to the evolut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
108
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(117 citation statements)
references
References 47 publications
8
108
1
Order By: Relevance
“…We avoid comparing our results with other analyses (e.g. Poggianti et al 2013b) which, although treating the evolution of the number density of compact galaxies, adopt a much lower cut in stellar mass with respect to our cut (e.g. ∼1−5 × 10 10 M ).…”
Section: Local Universementioning
confidence: 95%
See 1 more Smart Citation
“…We avoid comparing our results with other analyses (e.g. Poggianti et al 2013b) which, although treating the evolution of the number density of compact galaxies, adopt a much lower cut in stellar mass with respect to our cut (e.g. ∼1−5 × 10 10 M ).…”
Section: Local Universementioning
confidence: 95%
“…Valentinuzzi et al 2010;Carollo et al 2013)? A promising approach to shed light on the origin of the size evolution is to investigate how the number density of dense galaxies evolves over the cosmic time (Saracco et al 2010;Bezanson et al 2012;Cassata et al 2013;Poggianti et al 2013b;Carollo et al 2013;Damjanov et al 2014Damjanov et al , 2015. The analyses by various authors differ slightly in the selection of the sample, for example via passivity, visual classification, colour, and Sersic index; in the definition of so-called dense galaxies, selected for example on the basis of their mean stellar mass density Σ = M /2πR 2 e or sigma deviation from the local size-mass relation (SMR); and in the treatment of the progenitor bias.…”
Section: Introductionmentioning
confidence: 99%
“…The third scenario to explain the fast decline in the zero point of e Q S is that newly quenched galaxies at lower redshifts may arrive on the quiescent relation with significantly larger r e , and hence smaller e S , at a given mass than did earlier galaxies (e.g., Carollo et al 2013;Poggianti et al 2013). This is an example of the "progenitor bias" effect pointed out by van Dokkum & Franx (2001) S -than earlyevolving SFGs, giving some weight to this possibility.…”
Section: Is a Mass Loss) Thus The Ratio Between The Two Ismentioning
confidence: 98%
“…(2) Part of the increase in the overall radius can also be caused by additional processes, such as stellar mass loss associated with passive evolution (i.e., death of old stars), which causes adiabatic expansion (Damjanov et al 2011;Poggianti et al 2013;Porter et al 2014;. (3) Lastly, the strong decline in e Q S could also be caused by the arrival of new quiescent galaxies with progressively larger effective radii at lower redshifts (e.g., Carollo et al 2013;Poggianti et al 2013;Porter et al 2014). Each of these scenarios leads to a different evolution in the zero points of e Q S and 1 Q S , and thus we can test whether any of them matches the observed evolution in the ratio of zero points.…”
Section: Redshift Evolution Of the Zero Points Of The Quiescent Strucmentioning
confidence: 99%
“…Several studies have found a relation between the size and the age of passive galaxies at intermediate and high redshift (e.g., Valentinuzzi et al 2010;Poggianti et al 2013;Belli et al 2015;Shetty & Cappellari 2015, but see also Fagioli et al 2016 for different opinions), suggesting that the selection of old galaxies could minimize the descendant/progenitor mismatch. Following this idea, we select Coma galaxies whose ages are older than the difference between the look-back times of Coma and our highest redshift KCS overdensity (e.g., 9…”
Section: Distribution Of Galaxy Properties and Selection Effectsmentioning
confidence: 99%